Familial Effects on Intimate Partner Violence Perpetration Across Adolescence and Young Adulthood. (May 2018) - Kaufman-Parks, Angela M.; DeMaris, Alfred; Giordano, Peggy C.; Manning, Wendy D.; Longmore, Monica A.
Research suggests violence in the family-of-origin is a consistent predictor of later intimate partner violence (IPV). However, prior empirical studies have also demonstrated that exposure to violence does not lead deterministically to violent behaviors in young adulthood. Given that family context entails more than simply the presence or absence of abuse, additional aspects of family life warrant examination. One such aspect is the quality of the parent–child relationship. Using five waves of data from the Toledo Adolescent Relationships Study ( N = 950 respondents, 443 males and 507 females), the present study examined both main and interactive effects of parent–child physical aggression (PCPA) and parent–child relationship quality (PCRQ) in predicting adolescents' and young adults' IPV perpetration. Results indicated that both PCPA and PCRQ were key independent predictors of individuals' IPV perpetration, but did not interact to produce cumulatively different risk. Important interactions between PCPA and gender, and PCRQ and age were also found.